Topografski podatki in Geodetska uprava Republike Slovenije - Petek, Tomaž (Geodetski vestnik, 1998)
Digital topographic data systems consists of a topographic database containing the most detailed general topographic data with nation-wide coverage. This article describes a proposal for the provision of quality topographic data to users. Data structuring, storage and maintenance are proposed, and proposals are described for a data model and quality model prepared by the contractor who prepared the prototype solution.
Keywords: data model; kakovost topografskih podatkov; podatkovni model; survey method; topografska baza; topographic data quality; topographic database